Comparative study of conventional and hydromechanical deep drawing processes based on finite element analysis - Mohammed Abbadeni; Ibrahim Zidane; Hamou Zahloul; Zakaria Madaoui (Fracture and Structural Integrity)
A two-dimensional finite element analysis has been performed to investigate hydromechanical and conventional deep drawing processes. The effects of the fluid structure interaction on the material formability, the strain and the thickness distributions are investigated. Large plastic deformation is observed in the plank at the bottom and the corner of the punch. Plastic deformation distribution results show a difference between the hydromechanical deep drawing process and the conventional deep drawing which is due to the friction effect. This latter represents one of the major features of the hydromechanical deep drawing process. Concerning the formability of the blank, the obtained results show that the hydromechanical deep drawing process gives a better formability than the conventional deep drawing process.